2018
DOI: 10.33546/bnj.231
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Spiritual-Wellbeing With Anxiety and Depression in Patients With Cardiac Heart Disease

Abstract: Background: Anxiety and depression are problems faced by patients with chronic diseases such as patients with Coronary Heart Disease (CHD). Both of these can also worsen the condition of CHD patients, thus needs to be prevented and handled. It is stated that  spirituality can enhance constructive coping skills in patients with chronic diseases. But how it relates to anxiety and depression in patients with CHD  in Indonesia was still unknown.Objective: The study purpose was to identify the relationship of spiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…According to previous study that physical limitations made up by 42% of CHD patients, frequent angina and low patients satisfaction in medication respectively accounted for 56% and 58% (Nuraeni, Mirwanti, Anna, & Prawesti, 2016). Other study showed the low spiritual well-being of a fifth CHD patients (15%) (Nuraeni, Mirwanti, & Anna, 2018). Furthermore anxiety and depression in outpatient CHD patients was high, and generally, their quality of life as much as 58% was also low (Nuraeni et al, 2016).…”
Section: Introductionmentioning
confidence: 94%
“…According to previous study that physical limitations made up by 42% of CHD patients, frequent angina and low patients satisfaction in medication respectively accounted for 56% and 58% (Nuraeni, Mirwanti, Anna, & Prawesti, 2016). Other study showed the low spiritual well-being of a fifth CHD patients (15%) (Nuraeni, Mirwanti, & Anna, 2018). Furthermore anxiety and depression in outpatient CHD patients was high, and generally, their quality of life as much as 58% was also low (Nuraeni et al, 2016).…”
Section: Introductionmentioning
confidence: 94%
“…26 The GDS contains 30 items that are answered using a "yes/no" format. The total score ranges from 0 to 30, the individuals are categorized into three groups using the cut-off point: normal (0-9); mild depressives (10)(11)(12)(13)(14)(15)(16)(17)(18)(19); severe depressives (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The GDS has good reliability and validity in Chinese older adults.…”
Section: Depressive Symptommentioning
confidence: 99%
“…14 And it was associated with a reduced incidence risk of depressive symptoms among older adults with heart failure and/or chronic pulmonary disease. 15 In addition, individuals with high level of spirituality also have a significantly increased rate of depression remission over time among the patients with depression. 16 Despite the growing evidence of a link between spirituality and depressive symptoms in older adults under a diversity culture.…”
Section: Introductionmentioning
confidence: 99%
“…These factors were social support, anxiety, spiritual wellbeing, marital status, physical limitations, frequency of angina, and factors related to treatment history. These studies indicated that depression was associated with low spiritual wellbeing (Nur'aeni et al, 2019), anxiety (Nuraeni et al, 2018), and low social support (Chaerunnisa et al, 2017). Another aspect to be explored concerning depressive symptoms is patients' belief of illness or illness perception or illness cognition.…”
mentioning
confidence: 99%